Granulomatous Hepatitis: A Rare Case Report (BIRDEM Medical Journal, 2012)
Hepatic granulomas are found in about 3 to 10% of liver biopsies. In the liver, granulomas often merely serve as the morphologic clue to some underlying systemic process while liver function is well preserved. In approximately 15% of cases no aetiology can be established despite extensive investigations. Here we report a case of 43 years old lady with history of right upper quadrant pain with occasional fever and vomiting which was attributed to her gall bladder stones. Her liver function tests(LFT), hematological, biochemical test results were normal and all the viral markers were negative. During laparoscopic cholecystectomy, the liver was found to be studded with numerous grayish white small nodules. Liver biopsy was done which revealed non-caseating granulomatous hepatitis. DOI: http://dx.doi.org/10.3329/birdem.v1i1.12397 Birdem Med J 2011; 1(1): 51-53